2004
DOI: 10.1002/zaac.200300361
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Magnesium and Calcium Complexes containing the Rigid, Dianionic 1, 2‐Bis[(2, 5‐di‐tert‐butylphenyl)imino]acenaphthene (dtb‐BIAN) and 1, 2‐Bis[(2‐biphenyl)imino]acenaphthene (bph‐BIAN) Ligands

Abstract: The new rigid bidentate nitrogen ligands 1,2-bis [(2,5-ditert-butylphenyl)imino]acenaphthene (1) (dtb-BIAN) and 1,2bis[(2-biphenyl)imino]acenaphthene (2) (bph-BIAN) have been synthesized by condensation of 1,2-acenaphthylenedione with 2,5-ditert-butylaniline and 2-aminobiphenyl, respectively. Reduction of 1 and 2 with magnesium and calcium results in the formation of the monomeric metal complexes [(dtb-BIAN)Mg(THF) 2 ] (3), [(bph-Monomere Magnesium-und Calciumkomplexe mit 1,2-Bis[(2,5-di-tertbutylphenyl)imino]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 25 publications
(7 reference statements)
3
32
0
6
Order By: Relevance
“…This fact is consistent with the assumption that steric hindrance at the metal atom caused by the dtb BIAN ligand is larger than that caused by the dpp BIAN ligand. This is also confirmed by the fact that crystallization from a THF solution affords the (dtb BIAN)Mg(THF) 2 com plex with two coordinated solvent molecules, 10 whereas the (dpp BIAN)Mg(THF) 3 complex crystallizes with three solvent molecules. 9 The ESR spectrum of com plex 4 (see Fig.…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…This fact is consistent with the assumption that steric hindrance at the metal atom caused by the dtb BIAN ligand is larger than that caused by the dpp BIAN ligand. This is also confirmed by the fact that crystallization from a THF solution affords the (dtb BIAN)Mg(THF) 2 com plex with two coordinated solvent molecules, 10 whereas the (dpp BIAN)Mg(THF) 3 complex crystallizes with three solvent molecules. 9 The ESR spectrum of com plex 4 (see Fig.…”
Section: Methodssupporting
confidence: 67%
“…Recently, we have synthesized two new acenaphthenediimine ligands, viz., 1,2 bis[(2,5 di tert butylphenyl)imino]acenaphthene (dtb BIAN) and 1,2 bis[(2 biphenyl)imino]acenaphthene (bph BIAN), and prepared magnesium and calcium complexes with these ligands. 10 Recent studies demonstrated that the (dpp BIAN)Mg(THF) 3 complex, which is readily gener ated in situ, is highly reactive toward various organic com pounds. 11-13 Some reactions of this complex are accom panied by reduction of organic compounds and oxidation of the coordinated dpp BIAN dianion to the radical an ion to give paramagnetic complexes.…”
mentioning
confidence: 99%
“…14 Complexes 1-3 were synthesized according to pro cedures described earlier. 3,4 In all cases, solutions of complexes 1-3 in THF were prepared from the corresponding diimine (1.0 mmol) and an excess of magnesium metal and were used in hydrolysis in situ. Tetrahydrofuran, diethyl ether, and hexane were dried, stored over sodium benzophenone ketyl, and dis tilled immediately before use.…”
Section: Methodsmentioning
confidence: 99%
“…15 The synthe sis of two new BIAN ligands, viz., 1,2 bis[(2,5 di tert butylphenyl)imino]acenaphthene (dtb BIAN) and 1,2 bis[(2 diphenyl)imino]acenaphthene (dph BIAN), and their complexes with magnesium and calcium was documented. 16 The exchange reactions of GeCl 2 (C 4 H 8 O 2 ) with magnesium derivatives of the above three BIAN ligands afforded germylenes (dpp BIAN)Ge, (dtb BIAN)Ge, and (dph BIAN)Ge, which were struc turally characterized. 17 It was found that the (dpp BIAN)Mg(thf) 3 complex (1) readily reduces benzophenone, resulting in oxida tion of the dpp BIAN dianion to the radical anion and the formation of the corresponding pinacolate [(dpp BIAN) •-Mg(thf)] 2 [µ O 2 C 2 Ph 4 ] (2).…”
mentioning
confidence: 99%